Synthesis of polyhedral oligomeric silsesquioxane-n-acetylcysteine conjugate with click chemistry and ıts antioxidant response and biocompatibility - Açarı, İdil Karaca; Balcıoglu, Sevgı; Ates, Burhan; Koytepe, Suleyman; Yılmaz, İsmet; Seckin, Turgay (My University, 2020)
In this study, polyhedral oligomeric silsesquioxane-N-acetylcysteine (POSS-NAC) conjugateas a potential antioxidant molecule was synthesized from N-acetylcysteine (NAC) and aminofunctionalPOSS structure by click chemistry. The chemical structures and thermal propertiesof the synthesised POSS-NAC conjugate was characterized by spectroscopic and thermalanalysis techniques. The antioxidant capacity of the POSS-NAC conjugate was alsodetermined by the 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicalscavenging activity and reducing power methods. According to the reducing power method,POSS-NAC structure has lower reducing activity than standard ascorbic acid and trolox(p<0.001). It was found from the ABTS radical scavenging activity results that the synthesizedPOSS-NAC conjugate had a significantly higher radical scavenging effect than the standards(p <0.001). Biocompatibility properties of the POSS-NAC structure were detected in vitro cellculture system with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) teston L-929 mouse fibroblast cells. The synthesized POSS-NAC conjugate exhibits highantioxidant activity and good biocompatibility
Keywords: Malzeme Bilimleri; Biyomalzemeler